An investigation of dispositional mindfulness and mood during pregnancy - Adele Krusche; Catherine Crane; Maret Dymond (BMC, 2019)
Abstract Background Mindfulness courses are being offered to numerous groups and while a large body of research has investigated links between dispositional mindfulness and mood, few studies have reported this relationship during pregnancy. The aim of this study was to investigate this relationship in pregnant women to offer insight into whether an intervention which may plausibly increase dispositional mindfulness would be beneficial for this population. Methods A cross-sectional analysis was conducted to explore potential relationships between measures of mindfulness and general and pregnancy-specific mood. A sample of pregnant women (n = 363) was recruited using online advertising and community-based recruitment and asked to complete a number of questionnaires online. Results Overall, higher levels of mindfulness were associated with improved levels of general and pregnancy-related mood in pregnant women. Controlling for general stress and anxiety, higher scores for mindfulness in (psychologically) healthy women were associated with lower levels of pregnancy-related depression, distress and labour worry but this relationship was not apparent in those with current mental health problems. In participants without children, higher mindfulness levels were related to lower levels of pregnancy-related distress. Conclusions These results suggest a promising relationship between dispositional mindfulness and mood though it varies depending on background and current problems. More research is needed, but this paper represents a first step in examining the potential of mindfulness courses for pregnant women. Increasing mindfulness, and therefore completing mindfulness-based courses, is potentially beneficial for improvements in mood during pregnancy.